(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article conducts a critical analysis of the unique aesthetics of social realism employed by women writers from Northeast India. It posits that their fiction, written in English, functions as a powerful medium for the subaltern—a term encompassing the region’s communities marginalized by the dual forces of mainland Indian nationalism and internal patriarchy—to articulate its lived reality. Moving beyond classical social realism, which often prioritizes economic determinism; this study argues that the selected writers forge a distinct "intersectional realism." This mode of representation intricately weaves together the political (the insurgency-military complex), the geographical (the borderland identity), the ethnic (tribal and non-tribal dynamics), and the gendered (patriarchal constraints) to create a multi-layered narrative truth. Through close textual analysis of select novels—Mamang Dai’s The Black Hill (2014), Anjum Hasan’s Lunatic in my Head (2007), and Easterine Kire’s Bitter Wormwood (2011)—the article examines how these authors use specific narrative strategies: the infusion of indigenous myth and oral history to challenge monolithic national narratives, the centering of the everyday lives of women amidst conflict to humanize political strife, and the depiction of urban spaces like Shillong as sites of cultural negotiation. The research concludes that the social realism of Northeast women writers is not merely descriptive but profoundly agentive. It is an aesthetic of resistance and remembrance, a crucial intervention that decolonizes literary representation and allows the subaltern, in its myriad voices, to speak and be heard.